2015
DOI: 10.1007/s00216-014-8447-7
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution time and spatial imaging of tobacco and its pyrolysis products during a cigarette puff by microprobe sampling photoionisation mass spectrometry

Abstract: The time- and space-resolved chemical signatures of gases and vapours formed in solid-state combustion processes are difficult to examine using recent analytical techniques. A machine-smoked cigarette represents a very reproducible model system for dynamic solid-state combustion. By using a special sampling system (microprobe unit) that extracts the formed gases from inside of the burning cigarette, which is coupled to a photoionisation mass spectrometer, it was possible to study the evolution of organic gases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Combustion of tobacco results in both pyrolysis and pyrosynthesis of many harmful or potentially harmful constituents (HPHCs) [ 106 108 ]. As the health risk associated with CS is due to the HPHCs it contains, the main driver for risk reduction is the reduction in exposure to HPHCs.…”
Section: Apoe −/− Mouse Model To Investigate Toxicmentioning
confidence: 99%
“…Combustion of tobacco results in both pyrolysis and pyrosynthesis of many harmful or potentially harmful constituents (HPHCs) [ 106 108 ]. As the health risk associated with CS is due to the HPHCs it contains, the main driver for risk reduction is the reduction in exposure to HPHCs.…”
Section: Apoe −/− Mouse Model To Investigate Toxicmentioning
confidence: 99%
“…Zheng et al (2014) identified 67 gas-phase components in mainstream cigarette smoke using sorption tubes containing 3 beds of adsorbents (Carbopack C, Carbopack B and Carboxen III) analyzed using thermal desorption gas chromatography mass spectrometry (TD-GC-MS). Hertz-Schunemann et al (2015) studied the evolution of organic gases during a two-second cigarette puff using a novel microprobe to extract gases from inside a burning cigarette and analyzed them with a photoionization mass spectrometer. The concentrations of various pyrolysis and combustion products such as 1,3-butadiene, toluene, acetaldehyde and phenol were monitored at different sampling locations within cigarettes.…”
Section: Other Organicsmentioning
confidence: 99%
“…1, 2 It has been known for almost seven decades that free radicals are generated in high concentrations as a result of complex reactions in mainstream smoke. 37 Due to the presence of an unpaired electron, radicals are unstable, highly reactive and redox active.…”
Section: Introductionmentioning
confidence: 99%